A joint PDA data detection algorithm with MMSE channel estimation for uplink transmission of massive MU-MIMO system - Li, Lun; Shen, Dan; Tian, Xin; Chen, Genshe; Pham, Khanh; Blasch, Erik (2018 IEEE Aerospace Conference, 2018)
Massive multiple-input-multiple-output (MIMO), also known as a large-scale antenna system has been adopting by many 4G and 5G wireless communication standards due to its high data rate and outstanding link reliability. This paper considers a joint data detection scheme for uplink transmission of an L-cell massive multiple-user MIMO (MU-MIMO) system. In each MIMO cell, one base station with a large number of antennas communicates with multiple single-antenna users. A mathematical model is first proposed for received signals at a base station, and then a pilot-based minimum mean square error (MMSE) scheme is derived. A zero-forcing (ZF) data detection method is used to recover the transmitted signal, and categorize the interference by using the estimated channel information. The power of signal, interference, and noise are analyzed respectively. Then a more sophisticated probabilistic data association (PDA) detection algorithm with MMSE channel estimation is applied to jointly detect data with high accuracy. Finally, simulation results are presented to demonstrate that the proposed joint MMSE-PDA data detection algorithm outperforms the MMSE-ZF scheme.